The River Ythan Navigation, Aberdeenshire: The only natural inland waterway in northern Scotland - Redwood, Stewart D (Proceedings of the Society of Antiquaries of Scotland, 2024)
The River Ythan in Aberdeenshire is the only natural inland waterway in northern Scotland. It was navigable for about 10km from Newburgh, the port for Ellon since 1276, to the Meadow of Waterton, the landing place for Ellon. The peak of fluvial traffic was in the late 18th to early 20th centuries during the agricultural improvements for the import of manure fertiliser, bones, guano and coal, and the export of grain. Cargos were brought by coasters for 2.5km upriver to Newburgh where they were transhipped into lighters, which were sailed, poled or towed by a tug upriver to Meadow of Waterton. This article describes the harbour works, now largely demolished, by means of site inspections made from 1984 to 1986 and describes the history of this little-known example of fluvial transport, and the history of Newburgh as a coastal port. The Newburgh Quay at Culterty was built in 1842 by Mr Robert Black, a local shipowner, and is well preserved although the original buildings have been replaced by modern houses. The nearby Inches Pier was built by The Aberdeen Lime Company sometime between 1842 and 1866 on a small tidal islet. There was a long wooden pier to the low tide mark in the river channel, and a short causeway to the shore on the north side of the Foveran Burn. The pier was abandoned in c 1923 after the company’s coaster sank, and there are scant remains now. Docks were built at Meadow of Waterton probably in 1842 by Mitchell & Rae, agricultural and coal merchants, fertiliser manufacturers and shipowners (1840–1977). They consisted of two docks perpendicular to the river with warehouses. The East Dock was 30–49m long and 9m wide, and the West Dock was 61m long and 9m wide. The docks fell into disuse in 1924 and were infilled in the 1970s and 1980s, with no trace now. The upper navigation was closed in 1924, replaced by motor transport, while Newburgh continued to be used as a coastal port until 1968.